Analisis Pengaruh Gaya Hidup Dan Kualitas Pelayanan Terhadap Niat Pembelian Ulang Produk Makanan Cepat Saji Di Kota Surakarta Yang Dimediasi Oleh Perilaku Konsumen - Sari, Rohayani Mustika; Irmawati, Irmawati (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study explains type of research used in this study uses quantitative methods. The sampling technique used is purposive sampling with non-probability sampling. The analysis tool in this research is ads SEM PLS. The results of this study are 1.)Lifestyle has a positive and significant influence on the formation of consumer repurchase intention so that the first hypothesis is supported. 2.)Service quality has a positive influence on repurchase intention so that the second hypothesis is supported. 3.)The results of the analysis show that lifestyle has a positive influence on consumer behavior so that the third hypothesis is supported. 4.)Service quality has a positive influence on consumer behavior so that the fourth hypothesis is supported. 5.)There is a positive influence of consumer behavior on repurchase intention The fifth hypothesis is supported. 6.)Lifestyle has a positive and significant indirect influence on repurchase intention through the mediating variable of consumer behavior so that the sixth hypothesis is supported. 7.)Service quality provides a positive and significant indirect influence on purchase intention through the mediation variable of consumer behavior so that the hypothesis of